Pencegahan Kekerasan dalam Konflik Mahasiswa di Daerah Istimewa Yogyakarta - Yuliyanto Yuliyanto (Jurnal HAM, 2014)
The purpose of this study was to determine the factors that cause student conflicts, to describe the views and attitudes of students when dealing with conflict, and to depict the policy of the faculty member, police and local government in dealing with conflict prevention and conflict resolution. This study uses qualitative descriptive approach. The results of this study concluded that, first, the views and attitudes of students when dealing with conflict have been fundamentally different; Second, the violence that occurred in several universities have differences in terms of intensity and background of violence. Third, the policies issued by stakeholders have different dynamics amongst policy makers. Suggestions can be submitted based on this study including: students are expected to have a constructive view of the conflict; faculty members are expected to conduct needs assessment in student guidance; and the police members are expected to make a visual mapping of potential violence among students and create a dialogue between students and security forces.